A Strategic Approach to International Training: A Contingency Based Global Training Model - Hartman, David; Elahee, Mohammad (Journal of Comparative International Management)

(untitled) (Management Futures, 2013)
Training issues are complex regardless of the size or location of the actors involved. As firms make their way up the ladder of internationalization, the contextual nature of training as well as the limitations of its generalizability can inhibit its effectiveness in sharing between the various organizational sub-units, particularly those with different national cultures. In light of this, a model matching appropriately designed training regimens with the suitable type of international business operation is proposed in this paper. A number of propositions are also drawn from the model. The paper concludes with a discussion of the implications of the model and possible future research.